Novel photochromic 2,2´-bithiophene azo dyes - Coelho, Paulo J. (2009)
The photochromic behaviour of two series of 2,2’-bithiophene azo dyes in THF solutions was studied. The photochromic properties and colour constancy were strongly dependent on the substitution pattern of the dyes. Under visible irradiation (> 420 nm) while some dyes exhibited a significant change in the colour intensity others exhibited an almost stable absorption. The photokinetic parameters of these systems are described.